(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
This study investigates air entrainment through free surface both in vertical circular plunging jets and plunging breakers. Three scale modesldata of void fraction for identical froude numbers measured by Hoque and Chanson et al. have been used to investigate the scale effects. The results highlight the significant scale effects when the weber number is less than 1000 in vertical circular plunging jets, whereas it may be significant in the laboratory when the wave height is less than 0.30 m. Bangladesh J. Sci. Ind. Res. 41(3-4), 207-218, 2006